The Obsessive-compulsive Disorder (OCD) and its relationship with Generalized Anxiety Disorder(GAD) among a sample of pupils in education stage Basic - Slaimon, Reem; Alsaadi, Reema; Watfe, Maism (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to identify the Obsessive-compulsive Disorder (OCD) and its relationship with Generalized Anxiety Disorder (GAD) among pupils in Basic education stage Depending on the sample of (30) pupils from the pupils of Basic education in the schools of the province of Tartous , The researcher used the Arab gauge of (OCD) prepared by Ahmed Abdul Khaleq and (GAD) in children prepared by Dr. Viola Beblawi scale, and it adopted the researcher to gain access to the results at the expense of the Pearson correlation coefficient to measure the correlation between the two variables and test T Student of the difference between the averages and Slope coefficient to measure the predictive ability. The study found the presence of statistically significant correlation between (OCD) and (GAD) among respondents and it demonstrated a statistically significant differences in the proportion of (OCD) between males and females in the target sample disturbance differences in favor of females (females received higher grades than males on the obsessive-compulsive scale scores than males) , While the results did not indicate the existence of any differences in Anxiety between male and female respondents, The results also indicate that it is possible to predict the existence of (GAD) among individuals who suffer from (OCD) a high percentage .The search is over a number of proposal .